PENGARUH KONFLIK DAN STRES KERJA TERHADAP KEPUASAN KERJA PEGAWAI DI KANTOR CAMAT LUAHAGUNDRE MANIAMOLO KABUPATEN NIAS SELATAN - Wau, Martinus (Universitas Nias Raya, 2025)
The purpose of this study was to determine the effect of work conflict and stress on employee job satisfaction at the Luahagundre Maniamolo Sub-District Office, South Nias Regency. This type of research is quantitative. The data source of this research is from employees by using a questionnaire or questionnaire, with a population and sample of 30 respondents. The data analysis method used is the multiple linear analysis method. Based on the results of hypothesis testing research with a tcount value of 2.797X1, 2.879X2> t table 1.699, so the researchers concluded that there is an influence of conflict and job stress on employee job satisfaction at the Luahagundre Maniamolo Sub-District Office, South Nias Regency. The researcher suggests that employees of the Luahagundre Maniamolo Sub-District Office should use effective communication in conveying their opinions to avoid confusion, the Luahagundre Maniamolo Sub-District Office should be able to place their employees according to their expertise so that they can help achieve goals and improve and apply high work discipline, ensure that employees do not waste their time doing other things that have nothing to do with office work, and work with full responsibility.